2014
DOI: 10.1002/hep.27036
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 2 deficiency ameliorates alcoholic fatty liver but worsens liver inflammation and fibrosis in mice

Abstract: Aldehyde dehydrogenase 2 (ALDH2) is the major enzyme that metabolizes acetaldehyde produced from alcohol metabolism. Approximately 40~50% of East Asians carry an inactive ALDH2 gene and exhibit acetaldehyde accumulation after alcohol consumption. However, the role of ALDH2 deficiency in the pathogenesis of alcoholic liver injury remains obscure. In the present study, wild-type and ALDH2−/− mice were subjected to ethanol feeding and/or carbon tetrachloride (CCl4) treatment, and liver injury was assessed. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 42 publications
5
105
2
Order By: Relevance
“…Kwon et al reported increased levels of inflammatory cytokines in aldh2 knockout mice (Kwon et al, 2014). Our results show that pretreatment with JTX did not induce a significant decrease in the levels of Cyp2e1 and aldh2.…”
Section: Discussionsupporting
confidence: 43%
“…Kwon et al reported increased levels of inflammatory cytokines in aldh2 knockout mice (Kwon et al, 2014). Our results show that pretreatment with JTX did not induce a significant decrease in the levels of Cyp2e1 and aldh2.…”
Section: Discussionsupporting
confidence: 43%
“…In a subsequent study, the decrease of ALT level in Aldh2 knockout mice was reported to be sustained for as long as the ethanol loading was administered, whereas wild type mice showed elevation of serum ALT [60]. Moreover, a liver injury model induced with a high-fat diet and carbon tetrachloride also showed lower serum ALT values in Aldh2 knockout mice than in wild type mice [61].…”
Section: Effect Of Aldh2*2 On Indicators Of Excessive Drinkingmentioning
confidence: 91%
“…A different mechanism was suggested using liver injury models, in which interleukin-6-induced signal transducer and activator of transcription 3 relieve hepatic steatosis and result in lower serum ALT levels [61]. Supporting this finding, Yokoyama and colleagues [69] performed an epidemiological study on Japanese alcoholic men and reported that the serum triglyceride concentration was lower in ALDH2*1/*2 carriers than in ALDH2*1/*1 carriers (the least squares means adjusted for age and drinking amount were 103 and 113 mg/dL, respectively).…”
Section: Mechanism Of Liver Damage Amelioration Induced By Congenitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 50 % of East Asian subjects carry an inactive ALDH2 gene and exhibit acetaldehyde accumulation after alcohol consumption. Interestingly, compared with wild-type mice, ethanol-fed ALDH2-/-mice had higher levels of malondialdehyde-acetaldehyde (MAA) adduct and greater hepatic infl ammation, with higher hepatic interleukin (IL)-6 expression but lower levels of steatosis and serum alanine aminotransferase (ALT) [ 62 ].…”
Section: Ethanol Metabolism and Genetic Variants Infl Uencing Alcoholmentioning
confidence: 99%